Research on static and dynamics mechanical characteristics of flexible bearing in harmonic reducer. (22nd April 2020) - Caizhi, Zhu; Xiaojing, Wang; Zhaolun, Li; Jun, Liu; Jiaqi, Zheng
Flexible bearing is an important component of harmonic reducer which is widely used in automation equipment, especially in industrial robots. Studying its mechanical characteristics has great significance. In this article, the theoretical model of contact force between rolling elements and outer ring is established based on three bending moment equations, and the characteristics of CSF-40-80 flexible bearing are also studied by finite element method analysis. Analysis of equivalent stress at static state has shown that it already has large equivalent stress before load and that external load has a great influence on it. The dynamic and contact characteristics of it after actual assembly are also presented in this article. The displacements and velocities at different locations at different times of the movement are found to be different, which can provide a reference for the manufacture of flexible bearing.